2018
DOI: 10.1080/15569527.2018.1442842
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rutin on cisplatin induced oxidative retinal and optic nerve injury: an experimental study

Abstract: Concomitant rutin administration may prevent the detrimental effects of cisplatin on lipid peroxidation, oxidative stress and inflammation markers and may also avert the histopathological damage on retina and optic nerve. Further studies are warranted to determine the effects of cisplatin and rutin on eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Importantly, some chemotherapeutics, such as cisplatin and oxaliplatin, exhibit oxidative traits. In the case of oxaliplatin, this ability is proven to be linked to the pathogenesis of CIPN [ 65 , 66 , 67 ]. Should the observations be applied to CIPN caused by other types of chemotherapy, vitamin E could constitute a potentially excellent treatment option in this type of peripheral neuropathy.…”
Section: Vitamin Ementioning
confidence: 99%
“…Importantly, some chemotherapeutics, such as cisplatin and oxaliplatin, exhibit oxidative traits. In the case of oxaliplatin, this ability is proven to be linked to the pathogenesis of CIPN [ 65 , 66 , 67 ]. Should the observations be applied to CIPN caused by other types of chemotherapy, vitamin E could constitute a potentially excellent treatment option in this type of peripheral neuropathy.…”
Section: Vitamin Ementioning
confidence: 99%
“…The clinical usage of CP is restricted due to its severe dose‐dependent side effects (Bayindir et al, ; Eid, Abdelkader, Abd El‐Raouf, Fawzy, & El‐Denshary, ). Previous research showed that CP treatment caused damage to many tissues and organ systems, such as reproductive toxicity (Kaya et al, ), nephrotoxicity (Masuda, Inoue, Miyata, Mizuno, & Nanba, ), hepatotoxicity (Ciftci, Onat, & Cetin, ), ototoxicity (Bayindir et al, ), ocular toxicity (Taşlı et al, ) and neurotoxicity (Kaya, Ciftci, Cetin, Tecellioğlu, & Başak, ). Many previous studies on CP‐induced male reproductive system toxicity demonstrated that CP administration led to oxidative damage and apoptosis in testicular tissue, a decline in testes' weight, an increase in abnormal sperm rate and a decrease in sperm concentrations and motility (Aksu et al, ; Ciftci et al, ; Kaya et al, ; Saral et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of the chemotherapeutic agent should be clarified in order to allow the discovery of new therapeutic drugs to modulate the chemotherapeutic agent-induced optic nerve oxidative damage. The results of recent studies indicate the involvement of chemotherapeutic agents-induced oxidative stress in the optic nerve oxidative injury in the rats (Icel et al 2018;Taşlı et al 2018;Özkaya and Nazıroğlu 2020).…”
Section: Recent Developments On the Chemotherapeutic Agents-induced Oxidative Injury In Optic Nervementioning
confidence: 99%
“…The hydrogen peroxide is converted to water by the catalytic actions of catalase and glutathione peroxidase. Hence, the decrease of the antioxidants such as glutathione and glutathione peroxidase were reported in the cisplatin-induced optic nerve injury of rats, although the decreases of antioxidants are modulated by the antioxidant treatments such as curcumin, Pycnogenol, and rutin (Icel et al 2018;Taşlı et al 2018;Özkaya and Nazıroğlu 2020). In the oral presentation, I will summarize recent developments on the chemotherapeutic agents-induced oxidative injury in optic nerve.…”
Section: Recent Developments On the Chemotherapeutic Agents-induced Oxidative Injury In Optic Nervementioning
confidence: 99%